Nosferatu’dan günümüze sinemadaki vampir karakterinin değişimi ve “yanılgı” - Arkan, Gamze Nil (My University, 2014)
Korku, insanlığın varolmasıyla ortaya çıkan bir duygudur. Doğduğu andan ölüme kadar, kişinin hayatında yer alır. Çalışmanın birinci bölümünde, korku kavramının tanımına ve korku sinemasının tarihine değinilecektir. Ikinci ve üçüncü bölümlerde, vampir kavramının tanımı, sinemaya nasıl girdiği ve Nosferatu’dan itibaren günümüze kadar gelen vampirin, fiziksel özelliklerinin, sosyal yaşamlarının nasıl değiştiği incelenecektir. Son bölümde “Yanılgı” filminin oluşum süreci, post prodüksiyon süreci, senaryosu ve çekim senaryosu yer almaktadır. Korku, sinema, vampir, değişim

Fear, is an emotion that appears with the existence of humanity. From born to death, fear always protects its existence in human’s lifetime. First part of this study includes; the definition of fear and the history of horror cinema. Second and the third part in this study, it will be narrated that what does the vampire notion mean, how it has become one of the most popular genre in cinema history and also it will be searched that from Nosferatu to this era how vampire character has altered in physical conditions, living conditions, adaptation in social life. ın the last part of this study is about the process, post production, script and shooting script of the movie “Delusion”. Fear, cinema, vampire, alteration
Keywords: Korku; Sinema